2021
DOI: 10.1186/s12967-020-02686-1
|View full text |Cite
|
Sign up to set email alerts
|

The risk and added values of the atherosclerotic cardiovascular risk enhancers on prediction of cardiovascular events: Tehran lipid and glucose study

Abstract: Background In 2013 American College of Cardiology and the American Heart Association released a guideline on the management of atherosclerotic cardiovascular disease (ASCVD) including a composite of death from CVD, non-fatal myocardial infarction, or non-fatal stroke (hard CVD). This guideline recommended a risk score that was calculated using pooled cohort equations (ASCVD-PCE). The guideline was updated in 2018/2019 and further risk discussion was suggested for deciding whether to continue or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“… ever pregnant 10-y CVD age at menarche/menopause, menopausal status, HRT, gestational hypertension/diabetes, number of children, miscarriages, stillbirths b C-index 0.70 (0.67, 0.73) 0.70 (0.67, 0.73) n.s. TLGS (1) 90 10-y CVD hypertensive disorders of pregnancy C-index 0.52 (0.42, 0.61) 0.56 (0.49, 0.63) 10-y CVD gestational diabetes, macrosomia C-index 0.52 (0.42, 0.61) 0.60 (0.48, 0.74) TLGS (2) 89 19-y CVD placenta previa/abruption, preterm delivery, abortion, stillbirth, pregnancy-induced hypertension/pre-eclampsia, gestational diabetes, ectopic pregnancy c C-index 0.7798 (0.7602, 0.7974) 0.7851 (0.7677, 0.8041) <0.001 VIP 91 10-y CVD low birth weight offspring C-index 0.69 (0.67, 0.71) 0.69 (0.67, 0.71) 0.002 (−0.001, 0.006) 10-y CVD hypertensive disorders of pregnancy C-index 0.69 (0.67, 0.71) …”
Section: Risk Scoresmentioning
confidence: 99%
See 1 more Smart Citation
“… ever pregnant 10-y CVD age at menarche/menopause, menopausal status, HRT, gestational hypertension/diabetes, number of children, miscarriages, stillbirths b C-index 0.70 (0.67, 0.73) 0.70 (0.67, 0.73) n.s. TLGS (1) 90 10-y CVD hypertensive disorders of pregnancy C-index 0.52 (0.42, 0.61) 0.56 (0.49, 0.63) 10-y CVD gestational diabetes, macrosomia C-index 0.52 (0.42, 0.61) 0.60 (0.48, 0.74) TLGS (2) 89 19-y CVD placenta previa/abruption, preterm delivery, abortion, stillbirth, pregnancy-induced hypertension/pre-eclampsia, gestational diabetes, ectopic pregnancy c C-index 0.7798 (0.7602, 0.7974) 0.7851 (0.7677, 0.8041) <0.001 VIP 91 10-y CVD low birth weight offspring C-index 0.69 (0.67, 0.71) 0.69 (0.67, 0.71) 0.002 (−0.001, 0.006) 10-y CVD hypertensive disorders of pregnancy C-index 0.69 (0.67, 0.71) …”
Section: Risk Scoresmentioning
confidence: 99%
“…In addition, we screened reference lists of relevant articles to identify additional publications and found one further article. Among the 91 identified articles, nine [84][85][86][87][88][89][90][91][92] examined the added value of pregnancy-or reproductive-factors to already existing cardiovascular risk scores. An overview of the studies identified by our literature search is provided in Table 3.…”
Section: Added Predictive Value Of Female-specific Factorsmentioning
confidence: 99%
“…The metabolic syndrome (14) is a prime example of how a multiplicity of biomarkers can together predict ASCVD independently of the major risk factors (15)(16)(17)(18). Among its components are dyslipidemia, pro-inflammatory state, prothrombotic state, moderately elevated blood pressure, and dysglycemia/insulin resistance.…”
Section: Addressing An Aggregation Of Risk Biomarkers Factors In Individuals Is a Different Mattermentioning
confidence: 99%
“…Many of them can be considered metabolic risk factors, the same as or similar those as the metabolic syndrome (a multiplex risk factor for ASCVD (19) and a designated risk enhancing factor (20). An increased waist circumference is one independent predictor in the metabolic syndrome (18). Recent cholesterol guidelines (4) recognized moderate elevations of non-HDL-C, LDL-C, or apoB as a risk biomarker (Figure 5); since these 3 factors are highly correlated, the presence of more than one should not be double counted.…”
Section: Addressing An Aggregation Of Risk Biomarkers Factors In Individuals Is a Different Mattermentioning
confidence: 99%
“…Accordingly, in a study involving 47 metastatic melanoma patients treated with ipilimumab and RT, the abscopal effect emerged as being more successful with a reasonably hypo-fractionated dose inferior to 3 Gy compared to a dose higher than 3 Gy, which impaired the abscopal effect by abolishing cell-mediated immune responses [ 107 ]. In conclusion, all these observations suggest that radiation dosage and partition, along with the distinctive TME features, contribute to explaining the double-edged sword represented by RT in terms of immunoenhancement or immunosuppression [ 108 ]. More in-depth individual analyses are needed, together with reliable patient response markers, to identify how irradiation in combination with ICIs can be optimally turned into a therapeutic advantage [ 36 , 109 , 110 ], leaving open the option of a purinergic pathway blockade.…”
Section: Abscopal Effectmentioning
confidence: 99%